Perception of School Counsellors on Family Therapy as a Panacea to the Phenomenon of Empty Nest Syndrome in Southwest, Nigeria - Ayena, Olugbenga Oladapo; Shittu, John Idowu; Ojo, Segun Samuel (NIU Journal of Humanities; Vol 8 No 3 (2023): NIU Journal of Humanities, Vol. 8 No. 3, September 2023DO - 10.58709/niujhu.v8i3.1698, 2023)
This study examined the perception of school counselors on family therapy as a panacea to the phenomenon of empty nest syndrome in Southwest Nigeria. The target population of the study was all school counsellors in Southwest Nigeria. The sample consisted of 1200 school counsellors representing 200 from each of the six states of the Southwest Nigeria using the multi stage sampling approach. A questionnaire was self-developed by the researcher to collect data for the study. The content validity of the instrument was established and the instrument was subjected to reliability test using test retest approach in which Pearson’s Product Moment Correlation Coefficient formula was used to establish the coefficient. The Coefficient of 0.75 was obtained for the instrument which was considered high enough for the instrument. Four hypotheses were raised to pilot the study and the hypotheses were tested at 0.05 alpha level of significance. Data collected were analyzed using t-test statistics where two means were being compared while Analysis of Variance (ANOVA) were used to analyze data where more than two means were being compared. The findings of this study revealed that there were significant differences in respondents’ responses on family counseling as an antidote to empty nest syndrome based on religion [F(2,1197)=8.61;P<.05],  years of working experience [F(3,1196)=2.87;p<.05] and educational qualifications [F(3,1196)=3.32;P<.05], but there was no significant difference based on gender of respondents. The findings of this study have implications for school psychologists, school guidance counselors and educationists alike. It was therefore recommended that family therapy should be given a chance by practicing school counselors to help mitigate the effects of empty nest syndrome among parents in Southwest Nigeria. Keywords: School counsellors’ perception, Empty nest syndrome, Family therapy.